Implementasi Program Keluarga Harapan (PKH) di Kota Serang - Nazhwa Samrotul Aeni Aeni; Galuh Oktariyana; Alya Luthfiana Puspita; Aufrida Naila; Yaisy Acsun Awdovi (Fakultas Ilmu Sosial dan Ilmu Politik - Universitas Garut, 2024)
The focus of this journal is the implementation of the Family Hope Program (PKH) in Serang City. The central and local governments continue to study the problem of poverty, which is a social phenomenon. One of the underdevelopment factors that hinder a country's progress is a high poverty rate. The government continues to try to reduce poverty through various programs and assistance that directly touches the community, such as the Family Hope Program (PKH), which focuses on the poor in Serang City. However, there are still PKH recipients who are actually economically capable, and this should be a concern for PKH implementers because the main focus of this assistance is the poor. The Family Hope Program (PKH) has helped recipients in reducing the burden of education costs by providing funds to buy stationery, uniforms, and other educational needs. The program also has a positive impact on the economy of recipient families, such as being used as business capital. However, Kota Serang's human resources face obstacles in implementing the Family Hope Program (PKH) because they are unable to handle problems that do not meet the target of assistance. It is difficult to handle the problem of data that is not updated and is not accurate to the current situation of the recipients.